Not the typical winter cough. Issue 4 (23rd March 2007) - Parra Sanchez, G; Chetty, Govind; Sarkar, Pradip K
Abstract : We report on a young adult with a foreign body lodged in the right main bronchus for at least 5 days, with no alleged recollection of aspiration despite the size and shape of the object, which was removed successfully by rigid bronchoscopy.